Development of photochromic fused 2H-naphthopyrans with promising thermal fading rates. Issue 14 (11th March 2022) - Yan, Taishan; Tu, Xi; Xi, Zhiqiang; Du, Siyi; Han, Jie; Zhao, Bin; He, Zhengjie
Abstract : The effect of electronic and steric factors on the thermal fading rate (t1/2 ) of fused 2 H -naphthopyrans has been rationalized at the transition state level for the first time. The t1/2 can be tuned to 5 seconds by rational molecular design. Abstract : Tuning the thermal fading rate within several seconds while maintaining ideal colorability is a bottleneck problem for the industrial application of photochromic naphthopyrans. Herein, a series of new photochromic 2, 2, 6-triaryl 2 H -naphthopyrans and their benzannulated analogues with an isopropylidene link unit have been synthesized, and the thermal fading rates have been investigated using both experiments and theoretical calculations in this work. The factors affecting the photochromic performance of 2 H -naphthopyrans have been clarified at the transition state (TS) level for the first time. The results unveil that the fading process of 2 H -naphthopyrans is predominantly controlled kinetically, not thermodynamically. The thermal fading rate can be controlled at the level of several seconds by changing the steric repulsion of the fused ring units and the electrostatic repulsion of substituents. On the basis of the above findings, we have successfully developed several indeno-fused 2 H -naphthopyrans which possess promising thermal fading rates and excellent fatigue resistance.